Biochemistry - Campbell, Mary K (Thomson Brooks/Cole, 2006)
Discover how the latest developments in biotechnology, genomics, and proteins directly affect your life with Campbell/Farrell’s best-selling biochemistry text. Known for its logical organization and appropriate depth of coverage, BIOCHEMISTRY, Sixth Edition, balances scientific detail with readability that’s ideal for those studying biochemistry for the first time. A unique new magazine-style insert, Hot Topics in Biochemistry, introduces advancements in areas such as the Avian Flu, stem cell research, blood doping, HPV, the Gardasil vaccine, and more. New in-text questions help you master key concepts of biochemistry, while end-of-chapter problem sets, now grouped by problem types, assist you in efficiently preparing for exams. State-of-the art visuals throughout the book help clarify concepts. Biochemical Connections demonstrate how biochemistry affects other fields, such as health and sports medicine The book’s popular Web-based tutorial, CengageNOW for BIOCHEMISTRY, Sixth Edition, uses diagnostic tools and tutorials to help you focus your study time on the specific biochemistry principles that are challenging you personally. Count on BIOCHEMISTRY, Sixth Edition, for the most current coverage and clarity you need to excel in your one-semester biochemistry course.